Ferroptosis and metabolic syndrome and complications: association, mechanism, and translational applications - Zhou, Dongmei; Lu, Peipei; Mo, Xianglai; Yang, Bing; Chen, Ting; Yao, You; Xiong, Tian; Yue, Lin; Yang, Xi (Frontiers in Endocrinology, 2024)
Metabolic syndrome is a medical condition characterized by several metabolic disorders in the body. Long-term metabolic disorders raise the risk of cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). Therefore, it is essential to actively explore the aetiology of metabolic syndrome (MetS) and its comorbidities to provide effective treatment options. Ferroptosis is a new form of cell death that is characterized by iron overload, lipid peroxide accumulation, and decreased glutathione peroxidase 4(GPX4) activity, and it involves the pathological processes of a variety of diseases. Lipid deposition caused by lipid diseases and iron overload is significant in metabolic syndrome, providing the theoretical conditions for developing ferroptosis. Recent studies have found that the major molecules of ferroptosis are linked to common metabolic syndrome consequences, such as T2DM and atherosclerosis. In this review, we first discussed the mechanics of ferroptosis, the regulatory function of inducers and inhibitors of ferroptosis, and the significance of iron loading in MetS. Next, we summarized the role of ferroptosis in the pathogenesis of MetS, such as obesity, type 2 diabetes, and atherosclerosis. Finally, we discussed relevant ferroptosis-targeted therapies and raised some crucial issues of concern to provide directions for future Mets-related treatments and research.